2020
DOI: 10.1103/physrevlett.124.212504
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of Quantum Equilibration, Dissipation and Fluctuation in Nuclear Collisions

Abstract: Understanding the dynamics of equilibration processes in quantum systems as well as their interplay with dissipation and fluctuation is a major challenge in quantum many-body theory. The timescales of such processes are investigated in collisions of atomic nuclei using fully microscopic approaches. Results from time-dependent Hartree-Fock and time-dependent random-phase approximation calculations are compared for 13 systems over a broad range of energies. The timescale for full mass equilibration (∼2 × 10 −20 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 45 publications
(88 reference statements)
1
34
0
Order By: Relevance
“…It was found that the up limitation of impact parameter for synthsis of superheavy element Z = 116 was L = 56 h, mainly because the dissipatting energy of colliding system reached equilibrium almostly. The boundary line between CF and MNT have been found, which is around 5.7×10 −21 s. It is worth mentioning that our calculations for equilibrium timescales of fragment mass asymmetry and kinetic dissipation are consistant with those calculations from TDHF and TDRPA [60].…”
Section: Resultsmentioning
confidence: 51%
“…It was found that the up limitation of impact parameter for synthsis of superheavy element Z = 116 was L = 56 h, mainly because the dissipatting energy of colliding system reached equilibrium almostly. The boundary line between CF and MNT have been found, which is around 5.7×10 −21 s. It is worth mentioning that our calculations for equilibrium timescales of fragment mass asymmetry and kinetic dissipation are consistant with those calculations from TDHF and TDRPA [60].…”
Section: Resultsmentioning
confidence: 51%
“…where t s is the sticking time and t m is the mass equilibrium time constant, determined experimentally to be 5.2 × 10 −21 s [23]. This value later confirmed by fully microscopic calculations [54]. The mass ratio of the target-like nuclei is (1 − M R ).…”
Section: Discussionmentioning
confidence: 55%
“…For instance, the total kinetic energy of the fragments is well approximated by the Viola systematics [3,4], indicating a slow, damped relative motion of the fragments. In addition, the timescale for quasi-fission reactions [1,5,6] is of the same order as the minimum average timescale for the evolution from the compound system to the formation of the final fragments which is about 20 − 50 zs [7]. Another similarity is that both reaction mechanisms are impacted by quantum shell effects.…”
mentioning
confidence: 91%